Can a major AI conference shed its reputation for hosting sexist behaviour?. (29th November 2018) - Else, Holly
The Neural Information Processing Systems meeting is trying to be more inclusive, but a recent survey reveals there is a long way to go. The Neural Information Processing Systems is trying to be more inclusive but a recent survey paints an unflattering picture. Humanoid robot 'Sophia' appears to frown at the audience at a digital forum.